Liquid‐Phase Synthesis of Highly Deformable and Air‐Stable Sn‐Substituted Li3PS4 for All‐Solid‐State Batteries Fabricated and Operated under Low Pressures (Adv. Energy Mater. 8/2023). Issue 8 (24th February 2023) - Woo, Jehoon; Song, Yong Bae; Kwak, Hiram; Jun, Seunggoo; Jang, Bo Yeong; Park, Juhyoun; Kim, Kyu Tae; Park, Changhyun; Lee, Chanhee; Park, Kern‐Ho; Lee, Hyun‐Wook; Jung, Yoon Seok
Abstract : All‐Solid‐State Batteries In article number 2203292 by Yoon Seok Jung and co‐workers report on a liquid‐phase synthesis of a highly deformable and air‐stable sulfide solid electrolyte for solid‐state batteries. Marginal organic residues at the nanoscale for liquid‐phase‐derived Sn‐substituted Li3 PS4 remarkably enhance deformability, resulting in excellent electrochemical performance of the Li[Ni, Co, Mn, ]O2 electrodes, particularly when tailored at a low fabricating pressure or tested under low operating pressure.